2018
DOI: 10.7554/elife.36354
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale dysregulation of collagen structure-function disrupts mechano-homeostasis and mediates pulmonary fibrosis

Abstract: Matrix stiffening with downstream activation of mechanosensitive pathways is strongly implicated in progressive fibrosis; however, pathologic changes in extracellular matrix (ECM) that initiate mechano-homeostasis dysregulation are not defined in human disease. By integrated multiscale biomechanical and biological analyses of idiopathic pulmonary fibrosis lung tissue, we identify that increased tissue stiffness is a function of dysregulated post-translational collagen cross-linking rather than any collagen con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
128
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(157 citation statements)
references
References 62 publications
12
128
1
3
Order By: Relevance
“…1), consistent with fibrotic regions. It is now known there is marked difference in crosslinking in IPF relative to normal tissues, 34 where this could affect the net chirality. There are other possible underlying ECM changes as well, e.g., increased fibronectin deposition, 35 to which SHG is not directly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…1), consistent with fibrotic regions. It is now known there is marked difference in crosslinking in IPF relative to normal tissues, 34 where this could affect the net chirality. There are other possible underlying ECM changes as well, e.g., increased fibronectin deposition, 35 to which SHG is not directly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3,5,6 ] Increases in collagen cross‐linking have also been shown to be responsible for initial tissue stiffening in both lung and liver fibrosis, and to drive progressive fibrosis. [ 7,8 ]…”
Section: Fibrosis From a Materials Perspectivementioning
confidence: 99%
“…[ 45 ] Animal models of IPF have shown that collagen crosslinking (as opposed to increased collagen concentration) is a major reason for tissue stiffening and that inhibiting crosslinking limits stiffening and fibrosis‐related dysfunction. [ 8 ] Topography scans of collagen deposits in diseased tissue found that collagen fibers had smaller diameters and increased stiffness and crosslinking when compared with normal tissue.…”
Section: Mechanical Changes and Pathogenesis Of Fibrosis Across Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the utility of the multimodal SHG-LSM for biomedical studies we carry out a study of 3D lung fibroblast spheroids, confirming clear changes in the SHG signal when collagen production is promoted. Given that structure readouts of collagen provided by SHG imaging can allow diagnostic and prognostic information in cancer 49 and can also be markers of fibrotic lung disease 50 our 3D SHG-LSM approach can be transformative both for medical research and drug screening.…”
Section: Introductionmentioning
confidence: 99%